2015
DOI: 10.1080/14786435.2015.1091110
|View full text |Cite
|
Sign up to set email alerts
|

Structural properties, phase stability, elastic properties and electronic structures of Cu–Ti intermetallics

Abstract: The structural properties, phase stabilities, anisotropic elastic properties and electronic structures of Cu-Ti intermetallics have been systematically investigated using first principles based on the density functional theory. The calculated equilibrium structural parameters agree well with available experimental data. The ground-state convex hull of formation enthalpies as a function of Cu content is slightly symmetrical at CuTi with a minimal formation enthalpy (-13.861 kJ/mol of atoms), which indicates tha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
7
0
5

Year Published

2017
2017
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 35 publications
(14 citation statements)
references
References 63 publications
2
7
0
5
Order By: Relevance
“…En los contenidos superiores al 15% de titanio se ha observado que la combinación de Cu 3 Ti y CuTi 2 tienden a disminuir de manera acentuada la densidad del material, en razón a que estas fases son de estructura ortorrómbica y tetragonal. Las cuales en virtud de su cristalografía generan la formación de porosidad, ya que estas fases durante el proceso de sinterizado expanden el material al ocupar un mayor volumen; observándose en el Cu 3 Ti valores cercanos a 104,94 Å 3 [35] y 92,48 Å 3 [35] en el caso del CuTi 2 , en comparación a las materias principales de la matriz cobre-titanio que exhiben volúmenes de 47,67 Å 3 [33] y 35,46 Å 3 [33], respectivamente. Esto demuestra que la precipitación intermetálica tiene un papel importante en la formación de poro, debido a que el volumen que ocupan es mucho mayor en comparación a las fases en verde.…”
Section: Porosidad Y Densidadunclassified
See 2 more Smart Citations
“…En los contenidos superiores al 15% de titanio se ha observado que la combinación de Cu 3 Ti y CuTi 2 tienden a disminuir de manera acentuada la densidad del material, en razón a que estas fases son de estructura ortorrómbica y tetragonal. Las cuales en virtud de su cristalografía generan la formación de porosidad, ya que estas fases durante el proceso de sinterizado expanden el material al ocupar un mayor volumen; observándose en el Cu 3 Ti valores cercanos a 104,94 Å 3 [35] y 92,48 Å 3 [35] en el caso del CuTi 2 , en comparación a las materias principales de la matriz cobre-titanio que exhiben volúmenes de 47,67 Å 3 [33] y 35,46 Å 3 [33], respectivamente. Esto demuestra que la precipitación intermetálica tiene un papel importante en la formación de poro, debido a que el volumen que ocupan es mucho mayor en comparación a las fases en verde.…”
Section: Porosidad Y Densidadunclassified
“…De acuerdo a esto, la contracción durante el enfriamiento no es la suficiente para compensar el cambio de volumen y el transporte de masa de las reacciones de formación de los intermetálicos, de modo que dejan porosidad que incrementa el volumen total final del compuesto. Al seguir este proceso es presumible que la inclusión de contenidos de titanio mayores permitirá obtener una inclinación de las reacciones de difusión hacia fases cada vez menos densas con estructuras del tipo ortorrómbico, que en el espectro de intermetálicos del sistema exhiben los menores valores de densidad y energía de Gibbs [33].…”
Section: Porosidad Y Densidadunclassified
See 1 more Smart Citation
“…In the case of C 44 , it is interpreted as the resistance to monoclinic shear in the (100) plane, and is the critical parameter relating to the shear modulus. 64,65 In Table 2, the largest C 44 for HfRh 3 has suggested that HfRh 3 has the strongest resistance to shear in the (100) plane, while Hf 3 Rh 4 has the smallest C 44 to show the weakest resistance to shear in the (100) plane.…”
Section: Mechanical Propertiesmentioning
confidence: 99%
“…TC4 alloys have been broad utilized in petrochemical industry for their excellent corrosion resistance and high specific strength [1,2,3]. However, the poor thermal conductivity and wear resistance substantially restrict their large-scale application in oil and gas fields, especially as pipe coupling [4,5].…”
Section: Introductionmentioning
confidence: 99%